Using Hybrid Query Tree to Cope with Capture Effect in RFID Tag Identification - Haj Mirzaei, Milad; Ghiasbeigi, Masoud (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2015)
Tag collision is one of the important issues in RFID systems. Many algorithms were proposed to address this issue. One of these algorithms is Query Tree (QT) which is an effective method. In addition, RFID suffers from Capture Effect (CE). CE occurs when a reader identifies one tag in the presence of a collision. We consider this as a bad phenomenon for QT, because under CE reader will not identify all of collided tags. Besides, CE is good phenomenon for some algorithms like Dynamic Framed Slotted Aloha (DFSA), because it can identify one tag even in collision slots. So we combine QT and DFSA to improve the QT performance, then we evaluate our proposed algorithm, called Hybrid QT, to show that it outperforms other similar algorithms